Humic acid can mitigate the toxicity of small copper oxide nanoparticles to microbial decomposers and leaf decomposition in streams. (11th July 2016) - Pradhan, Arunava; Geraldes, Paulo; Seena, Sahadevan; Pascoal, Cláudia; Cássio, Fernanda
Summary: As the use of copper oxide nanoparticles (nanoCuO) in consumer products grows, aquatic ecosystems are likely to receive increasing amounts of these nanomaterials. Dissolved organic matter (DOM) may interact with nanoparticles and reduce their reactive surface area, which, in turn, can influence the impact of nanoCuO on organisms and ecological processes. We conducted a microcosm experiment to investigate the impacts of three size classes of nanoCuO (12, 50 and 80 nm mean diameter of the primary particles; five levels up to 400 mg L −1 ) and humic acid (three levels up to 100 mg L −1 ), as a major component of DOM, on microbial decomposers and leaf decomposition as an important ecosystem process in forest streams. Exposure to nanoCuO for 20 days reduced decomposition rate and fungal and bacterial biomass, fungal sporulation and spore diversity associated with the decomposing leaves. The effects were stronger as nanoparticle size decreased and the specific surface area increased. More dissolved ionic copper was released from the small nanoparticles, suggesting that Cu 2+ could have played a role in the observed size‐dependent toxicity of nanoCuO. Bacteria appeared to be more sensitive to nanoCuO than fungi since nanoparticles reduced the biomass of bacteria at lower concentrations than that of fungi (EC20 was 22 times lower for small and medium‐sized nanoparticles, and five times lower for large particles). However, fungal sporulation was the variable most sensitive to nanoCuO exposure (EC20 = 0.2 mg L −1 for the small nanoparticles). Microbial activity on the decomposing leaves was also inhibited by exposure to humic acid alone. However, humic acid also mitigated the adverse effects of the small and medium‐sized nanoCuO on both the microbial decomposers and leaf decomposition. Overall, our microcosm experiment indicates that nanoCuO toxicity to microbial decomposers and leaf decomposition depends on particle size and the presence of DOM. This highlights the importance of considering environmental context and the specific properties of particles to assess toxicity of nanomaterials in stream ecosystems.